Технологии и методы сортировки шлифпорошков из синтетических алмазов по форме и шероховатости поверхности зерен - Новиков, Н.В.; Никитин, Ю.И.; Богатырева, Г.П. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The results of basic and applied research regarding the developed nonstandard equipment and technologies of producing high-quality grinding powders of synthetic diamond of various grades and grain sizes suitable for the production of tools working under severe conditions in mining and metal working industries have been set out. It is shown that on the basis of the made in the ISM of the NASU high-performance equipment for selective crushing of diamonds, sieve classification, separation by grain shape and roughness there have been developed optimal conditions and technological processes for producing grinding powders of wide range and high quality factors which ensures the production of diamond tools in accordance with up-to-date needs of the national economy of Ukraine.